Selection of the optimal technology for surface mining by multi-criteria analysis - STOJANOVIC, CVJETKO; BOGDANOVIC, DEJAN; UROSEVIC, SNEZANA (Kuwait Journal of Science, 2015)
The selection of optimal technology for surface mining of mineral deposits is a standarddecision-making problem. The aim of this paper is to demonstrate the potential of thecombined AHP and ELECTRE methods in selecting the optimal technology usingthe open pit coal mine “Ugljevik East” (Ugljevik Istok) as an example. In order toresolve the problems encountered, the three types of technologies were taken intoconsideration with regards to the eight criteria for selecting the optimal solution. Thecriteria include the most important aspects of selecting the optimal technologies, suchas geology and geotechnical engineering, ecology, economy, etc. In addition, AHP isused to analyse the structure of the technology selection process and to determine thesignificance and impact of certain criteria in the selection process, while ELECTREmethod is used for the final ranking of alternatives. The obtained results indicate thatthe proposed combined method provides extraordinary results and that it can be used toresolve various, even the most complex problems that occur in mining engineering.